A Quantitative Proteomic Analysis of Brassinosteroid-induced Protein Phosphorylation in Rice (Oryza sativa L.) - Hou, Yuxuan; Qiu, Jiehua; Wang, Yifeng; Li, Zhiyong; Zhao, Juan; Tong, Xiaohong; Lin, Haiyan; Zhang, Jian (Frontiers in Plant Science, 2017)
The group of polyhydroxysteroid phytohormones referred to as the brassinosteroids (BRs) is known to act on plant development and the stress response. BR signal transduction relies largely on protein phosphorylation. By employing a label-free, MS (Mass Spectrometry)-based phosphoproteomic approach, we report here the largest profiling of 4,034 phosphosites on 1,900 phosphoproteins from rice young seedlings and their dynamic response to BR. 1,821 proteins, including kinases, transcription factors and core components of BR and other hormone signaling pathways, were found to be differentially phosphorylated during the BR treatment. A Western blot analysis verified the differential phosphorylation of five of these proteins, implying that the MS-based phosphoproteomic data were robust. It is proposed that the dephosphorylation of gibberellin (GA) signaling components could represent an important mechanism for the BR-regulated antagonism to GA, and that BR influences the plant architecture of rice by regulating cellulose synthesis via phosphorylation.